Observational Pharmacoepidemiology in the Drug Safety and Effectiveness Evaluation - José Cabrita; Ana Paula Martins (Formifarma, LDA., 2017)
Observational epidemiological studies have been used in the medicines context for more than 40 years, contributing to characterize drug use patterns and safety, efficacy and effectiveness profiles. Its use has been increased in recognition of the clinical trials limitations to assess the therapeutic and iatrogenic potential of the medicines after its commercialization. The evolution of the regulatory framework for pharmacovigilance, requiring post-marketing studies, post-authorization safety studies (PASS) and the post-authorization efficacy studies (PAES) to approve certain drugs, reinforced the importance of observational pharmacoepidemiology for the characterization of the medicines safety and effectiveness profiles. Pharmacoepidemiological research can be carried out from field studies designed to obtain the necessary information or in databases with health records of population samples that already contain the information. This 2nd option is more efficient and more and more frequent. Although, observational research from field studies continues to have its space, the increasing availability of databases allowed a new development to observational pharmacoepidemiology. Indeed, access to automated records databases with up-to-date information on medical prescriptions and global health care to representative population samples with long follow-up periods is a valuable tool for the study of drug use patterns and therapeutic and iatrogenic potential in routine clinical practice. In this context, observational pharmacoepidemiology reinforces its role as a scientific area particularly suitable for evaluating the safety and the effectiveness of the medicines in the "real world", making a relevant contribution to overcome the gap in translating the evidence from the clinical trials for clinical practice.